Effect of Internal Current Flow During the Sintering of Zirconium Diboride by Field Assisted Sintering Technology. Issue 1 (24th September 2015) - Gonzalez–Julian, Jesus; Jähnert, Kevin; Speer, Kerstin; Liu, Limeng; Räthel, Jan; Knapp, Michael; Ehrenberg, Helmut; Bram, Martin; Guillon, Olivier
Abstract : Effect of electric current on sintering behavior and microstructure evolution of zirconium diboride (ZrB2 ) was investigated using three different configurations of Field Assisted Sintering Technology/Spark Plasma Sintering. The current flow through the ZrB2 compact was controlled by modifying the interface between the graphite punches and the electrical conductive powder. Boron nitride discs, graphite foils or direct contact with the graphite punches were the three different interfaces used in order to deflect, conduct or promote, respectively, the current during the sintering process of the electrically conductive ZrB2 ceramics. The current flow during the sintering process triggered the elimination/reduction in B2 O3, leading to faster diffusion rates at high temperatures and limiting the formation of B4 C secondary phase. This allows to control the final density, grain size (from 19.6 to 43.2 μm) and secondary phase formation (from 5.95 to 11.61 vol%) as well as the electrical resistivity (from 7.7 to 9.4 μΩ·cm) of the specimens.